2022
DOI: 10.1111/apa.16453
|View full text |Cite
|
Sign up to set email alerts
|

Changes in perceived parental self‐efficacy after a Child‐Centred Health Dialogue about preventing obesity

Abstract: Childhood obesity is a global health burden that is likely to persist into adulthood and lead to the development of various comorbidities. 1 It tends to have its roots in the preschool years and affects children's immediate health, educational achievements and quality of life. That is why there is an urgent need to prevent obesity and promote healthy lifestyle behaviours at early age. 1 Food intake and physical activity behaviours are seen as modifiable determinants of childhood obesity. Negative indications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[ 50 ] where PSE was a positive predictor of children’s intakes of fruits and vegetables in a kindergarten based randomized controlled trial ( n = 558). Correspondingly, a child-centered health dialogue (i.e., a face-to-face intervention) at the age of 4 years within Swedish primary child health care [ 51 ] resulted in a positive effect on maternal PSE for promoting healthy physical activity behaviors. Altogether, it is reasonable to conclude that our findings and existing literature suggest that PSE may be an important target for health promotion in preschool-aged children.…”
Section: Discussionmentioning
confidence: 99%
“…[ 50 ] where PSE was a positive predictor of children’s intakes of fruits and vegetables in a kindergarten based randomized controlled trial ( n = 558). Correspondingly, a child-centered health dialogue (i.e., a face-to-face intervention) at the age of 4 years within Swedish primary child health care [ 51 ] resulted in a positive effect on maternal PSE for promoting healthy physical activity behaviors. Altogether, it is reasonable to conclude that our findings and existing literature suggest that PSE may be an important target for health promotion in preschool-aged children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a kindergarten based randomized controlled trial by Möhler et al [148] PSE was a positive predictor of children's intakes of fruits and vegetables. Derwig et al also observed a positive effect on maternal PSE for promoting healthy physical activity behaviors, following their face-to-face delivered intervention which was a child-centered dialogue also set in primary child health care [149]. Collectively, these findings as well as available literature suggest that targeting PSE may be important for health promotion in children during the preschool years [148,[150][151][152].…”
Section: Effectiveness On Pse (Paper Ii: Secondary Outcome)mentioning
confidence: 91%
“…The exceptions were in the subgroup analyses where the interventions had beneficial impact. 40,53,54 Perhaps this could be one of the pathways that needs to be further targeted for future interventions to be successful.…”
Section: Other Outcome Smentioning
confidence: 99%
“…However, neither of the two projects just discussed, and the first of the four healthy school start projects, reported that their interventions had a positive effect of the intervention on parental self‐efficacy. The exceptions were in the subgroup analyses where the interventions had beneficial impact 40,53,54 . Perhaps this could be one of the pathways that needs to be further targeted for future interventions to be successful.…”
Section: Other Outcomesmentioning
confidence: 99%